Uma proposta de construção de curvas planas no Geogebra - Arminio, Cassiano (2017)
This work is a proposal to construct plane curves using GeoGebra, a software of dynamic Mathematics, which has several algebraic and geometric tools. Some of the chosen plane curves are studied in high school, and others are of a level close to that developed in high school. The plane curves are analyzed from their parametric or cartesian definition equations. Using GeoGebra, constructions can be animated and modified, so that we can understand in detail the effects on graphs variations as parameters are modified.